Efektivitas Layanan Bimbingan Kelompok Dengan Teknik Sosiodrama Terhadap Perilaku Phubbing Pada Siswa Smp Negeri 42 Semarang - Ghozi, Ghozi Muhammad Muflih Abdurrozzak; Fitriana, Siti; Ismah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
The background of this study is the many problems of Class IX students in Public Middle School 42 Semarang who experience phubbing behavior. There are students who listen less and tend to hurt and ignore their interlocutors, because students focus more on their smartphonenas. The aim of this study is to know the effectiveness of the sociodrama engineering group guidance service for phubbing behavior. This research uses quantitative experimental research methods with the type of True-Experimental Design research. The population in this study was Semarang's 42th grade IX Middle School students except IX B which was used to do tryouts, so the population in this study was 5 classes totaling 164 students. Samples taken 1 class were 32 students divided into two groups namely the control group and the experimental group. The sampling technique in this study is the random sampling cluster. Data collection techniques use the likert scale, which is the scale of phubbing behavior. Based on the results of the paired sample t-Test test which shows that the signification value (2-tailed) of 0.010 < 0.05 means that there is the effectiveness of the sociodrama engineering group guidance on the phubbing behavior of Class IX students in Public Middle School 42 Semarang.